DETERMINAN DEPRESI PADA LANJUT USIA DI PANTI JOMPO HARAPAN JAYA MARELAN MEDAN - Ganda Sigalingging (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2017)
Insomnia usually that occur in the elderly, but can be a serious mental health problem that leads to depression. This condition will affect the quality of life of the elderly. The purpose of this survey study was to analyse the relation Insomnia with of depression for elderly in Panti Jompo Harapan Jaya Marelan. This study adopted the survey analytic with cross-sectional design. The population of this research are all of 66 respondents, with sampel of research are all of 66 respondents selected with total sampling technique. The data analyzed by using chi-square. The result of study there is relationship Insomnia with of depression for elderly in Panti Jompo Harapan Jaya Marelan Medan, with p value 0,003 (p = < α 0,05). Conclusion there is relationship Insomnia with of depression for elderly in Panti Jompo Harapan Jaya Marelan Medan. The management of panti Jompo Harapan Jaya Marelan Medan, create a conducive environment, to arrange regular sleep schedule, to give time to enjoy togetherness among fellow elderly with sport together, sing along with the ability of elderly also maintain spiritual by presenting religious leaders.